Kurdish websites' interest in covering cinematic topics - Saifalddin Hawija, Khanda; Ali Ahmad, Fuad (Zanco Journal of Human Sciences, 2023)
This research, titled (Kurdish websites' interest in covering cinematic topics) focuses on Kurdish websites whose contents are related to the cinema. The research problem is focused on this particular point: To what extent the Kurdish websites are interested in publishing cinematic topics? Linking media and cinema as two important pillars in the communication process, considering cinema as a means of entertainment and an important industry and at the same time as a means of guiding and educating society is a pillar of this research. The main objective of this research is to highlight the extent of interest in cinematic topics published by Kurdish websites. The total number of sites that were sampled in this study is twelve sites consisting of (Kurd Cinema, Kurd Film, Kurd Movie, Kurd Subtitle, Filmsazan, Tulip Cinema, Beenar, Shafilm, Kurding, Kurddoblazh, Kurdio Anime, Kurd Plus Anime). Due to the lack of a publication timeline, the researcher received a total of the twelve sites' topics until the end of the actual work of each of these sites. The researcher used the descriptive and survey method, and content analysis and survey forms were the tools used to collect data in this study. Where in the content analysis, the information was listed in five tables for each of these sites, and a 15-section questionnaire was distributed to 30 people with cinematic experience, to reinforce the information, which answers the research’s questions, and led to the conclusion that Kurdish websites allocated reasonable spaces for cinematic topics and were interested in publishing them, and digital platforms have strengthened the relationship between media and cinema, allowing the Kurdish audience to learn more about cinematic topics, in addition to many other results.